Making decisions for surgical intervention in neonates with necrotizing enterocolitis and the selection of appropriate surgical intervention - MEMİŞOĞLU, ASLI; KIYAN, GÜRSU; KARADENİZ CERİT, KIVILCIM; ERGELEN, RABİA (MARMARA UNIV, FAC MEDICINE, 2017)
Objective: Necrotizing enterocolitis (NEC) is one of the most common conditions requiring surgical intervention in the neonatal period. The decision for surgical intervention in NEC is difficult and the surgical procedures differ according to the condition of the patient. This study assesses the decision for surgical intervention in patients being followed with a preliminary diagnosis of NEC and the appropriate surgical procedure. Material and Method: The files of patients undergoing surgery with a diagnosis of NEC at the Marmara University Hospital Neonatal Intensive Care Unit between 15.07.2013-15.07.2015 were studied retrospectively. Patients were evaluated for the following: gestational age, birth weight, gender, time of onset of symptoms, abdominal distention, tenderness, presence of abdominal erythema, hypotension, acidosis, thrombocytopenia, radiological findings, surgical timing and post-operative follow up. Results: A total of 10 neonates (7 boys, 3 girls) were treated surgically with an NEC diagnosis. The average gestational age of the patients was 27.6 weeks (22-37 weeks), and the median birth weight was 710 grams (400-3750). Average onset of symptoms was found to be 8.1 days (2-30) postnatally. Abdominal distention and tenderness (10), hypotension (4), and abdominal erythema (3) were observed in patients upon physical examination. Acidosis (7) and thrombocytopenia (6) were observed in patients in laboratory findings. Free fluid (4), thickening of the intestinal wall ans (3), pneumatosis intestinalis (1), portal venous gas (1) were observed in patients during the assessment of the abdominal ultrasonography (US). Three patients whose direct x-ray evaluations were grade III underwent peritoneal drainage. The drain site of one of these patients closed by itself, and there was no need for further surgery for the patient. Laparotomy was carried out a day after clinical stabilization was achieved. Our third patient, the lowest birth weight in our series, was lost immediately following the peritoneal drainage process. Peritoneal drainage was planned in two other grade III patients based on the radiological findings. However, due to the appearance of necrotic bowel segments from the incision site, they underwent bowel resection and ileostomy during a bedside laparotomy. One of these patients improved clinically, but the other patient was lost in the early stages. Due to the deterioration seen in the clinical findings of 5 patients who were radiologically grade II, the decision for laparotomy was made initially. All of these 5 patients were discharged after an uneventful postoperative period. Conclusion: In patients who are grade II radiologically, the decision for surgical intervention in an operating room can be made according to clinical deterioration. In infants who are grade III, and whose clinical condition is poor, bedside surgical intervention in the neonatal intensive care unit is preferable..
Keywords: Necrotizing enterocolitis; Surgery; Laparotomy; Neonatal intensive care unit; Prematurity; INTENSIVE-CARE-UNIT; PERITONEAL DRAINAGE; INTESTINAL PERFORATION; LAPAROTOMY; INFANTS; PREVENTION